Pengaruh Direct Teaching Instruction dalam Meningkatkan Kemampuan Passing Atas Bola Voli Kelas VIII-A di MTs Ciniru - Aldi Agustin; Didi Muhtarom; Boby Agustan (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to determine the effect of the direct teaching instruction learning model on student on volleyball passing at MTs Ciniru. This research is quantitative research with the design used is one group pretest-posttest design. The subjects f this research were class VIII students at MTS Ciniru, and the sample used was 15 students. The research instrument used was a test on students in carrying out upper passing learning. The research results obtained tcount of 23,196 and t tabel value of 1.753. Therefore, the value of tcount >ttabel means it can be concluded that the direct teaching instruction method can improve the upper passing ability of class VIII students at MTs Ciniru. The magnitude of the increase in upper passing ability, after being given direct teaching instruction training to class class VIII/A students at MTs Ciniru.